2013
DOI: 10.1158/1078-0432.ccr-12-3017
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Pathways: Comparing the Effects of Drugs and T Cells to Effectively Target Oncogenes

Abstract: Mutant cancer-driving oncogenes are the best therapeutic targets, both with drugs like small-molecule inhibitors (SMI) and adoptive T-cell therapy (ATT), the most effective form of immunotherapy. Cancer cell survival often depends on oncogenes, which implies that they are homogenously expressed by all cancer cells and are difficult to select against. Mutant oncogene-directed therapy is relatively selective, as it targets preferentially the oncogene-expressing cancer cells. Both SMI and ATT can be highly effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 64 publications
(76 reference statements)
0
9
0
Order By: Relevance
“…We targeted two different epitopes of SV40 large T (T-Ag) in tumors whose growth depended on T-Ag ( Anders and Blankenstein, 2013 ). The H2-K b –presented peptide IV (pIV) is dominant, with ∼11% of the CD8 + T cells in T-Ag immunized wild-type mice being pIV specific, demonstrating that the epitope is efficiently processed and presented under vaccine conditions ( Mylin et al, 2000 ).…”
Section: Introductionmentioning
confidence: 99%
“…We targeted two different epitopes of SV40 large T (T-Ag) in tumors whose growth depended on T-Ag ( Anders and Blankenstein, 2013 ). The H2-K b –presented peptide IV (pIV) is dominant, with ∼11% of the CD8 + T cells in T-Ag immunized wild-type mice being pIV specific, demonstrating that the epitope is efficiently processed and presented under vaccine conditions ( Mylin et al, 2000 ).…”
Section: Introductionmentioning
confidence: 99%
“…First, they directly and specifically kill IGF1R + cancer cells even at a low level of surface expression as CD8 + CTLs are capable of responding to a single antigen molecule [ 48 ]. Second, they produce TNF-α and IFN-γ cytokines, which subsequently mediate bystander elimination of stromal cells and vasculature within the tumor microenvironment [ 49 ]. Third, they persist for months and years, and proliferate in vivo as it has been shown in recent clinical trials with CD19 CARs containing 4-1BB or CD28 signaling domains [ 1 , 3 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another reason for therapy failure might have been the tumor burden; perhaps, z-CAR-Ts would have been more effective against smaller tumors (27). Both antigen-dependent and -independent mechanisms can contribute to stroma destruction as a requirement for cancer eradication (28). Previous studies of TCR-mediated ATT consistently reported that tumor stroma targeting was critical to prevent tumor recurrence and that T-cell-produced IFNg needed to act on the tumor stroma (8,11).…”
Section: Discussionmentioning
confidence: 99%